2023
DOI: 10.3389/fcell.2022.1092161
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary signaling proteins are mislocalized in the brains of Bardet-Biedl syndrome 1-null mice

Abstract: In the brain, primary cilia are found on most, if not all, central neurons. The importance of neuronal cilia is underscored by the fact that human diseases caused by primary cilia dysfunction, which are known as ciliopathies, are associated with neuropathologies, including neuropsychiatric disorders and learning and memory deficits. Neuronal cilia are enriched for certain G protein-coupled receptors and their downstream effectors, suggesting they sense and respond to neuromodulators in the extracellular milieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…To assess the performance of our atlas alignment and lift-over annotations, we first confirmed the enrichment of genes within certain brain regions. Consistent with previous studies, we found Grm2 to be visually primarily enriched in the dentate gyrus 11 , Sstr2 to be enriched in cerebral cortical layers 5 and 6 12 , and Gpr161 to be enriched in the CA1 13 Next, we took a more agnostic approach to assess the performance of our atlas alignment and lift-over annotations by evaluating the consistency of cell-type compositional heterogeneity within brain structures across replicates. Consistent with previous studies 14 , we observed cell-types to be spatially and compositionally variable across brain regions.…”
Section: Stalign Enables Alignment Of Single-cell Resolution St Datas...supporting
confidence: 79%
“…To assess the performance of our atlas alignment and lift-over annotations, we first confirmed the enrichment of genes within certain brain regions. Consistent with previous studies, we found Grm2 to be visually primarily enriched in the dentate gyrus 11 , Sstr2 to be enriched in cerebral cortical layers 5 and 6 12 , and Gpr161 to be enriched in the CA1 13 Next, we took a more agnostic approach to assess the performance of our atlas alignment and lift-over annotations by evaluating the consistency of cell-type compositional heterogeneity within brain structures across replicates. Consistent with previous studies 14 , we observed cell-types to be spatially and compositionally variable across brain regions.…”
Section: Stalign Enables Alignment Of Single-cell Resolution St Datas...supporting
confidence: 79%
“…Second, it is entirely possible that cAMP production by GPR161 has roles in adult tissues outside of the Hedgehog pathway. Indeed, GPR161 is expressed in many different cell types in adult tissues that are not hedgehog regulated, such as the adult hippocampus CA1 region 59 . GPR161 has also been reported to localize to cilia of hippocampal neurons 1,59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GPR161 is expressed in many different cell types in adult tissues that are not hedgehog regulated, such as the adult hippocampus CA1 region 59 . GPR161 has also been reported to localize to cilia of hippocampal neurons 1,59,60 . Ciliary peptidergic GPCR signaling in the CA1 pyramidal neurons has been recently shown to regulate chromatin accessibility 61 , but the role of cAMP signaling mediated by cilia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in regulating the enrichment of GPCRs within the cilium. For example, SSTR3, NPY2R and MCHR1 fail to accumulate in neuronal cilia in multiple brain regions in the absence of BBS1, BBS2, and BBS4 ( Berbari et al, 2008 ; Loktev et al, 2013 ), and BBSome disruption induces ciliary accumulation of DR1R, GRP19, and hedgehog pathway receptors ( Domire et al, 2011 ; Ye et al, 2018 ; Stubbs et al, 2023 ). Overall, it appears that the BBSome may select proteins for IFT-dependent trafficking and contribute to IFT train formation at the base and tip, potentially through stabilizing interactions between IFT-A and IFT-B ( Blacque et al, 2004 ; Wei et al, 2012 ; Williams et al, 2014 ).…”
Section: Primary Ciliummentioning
confidence: 99%